Adjuvant Radiotherapy for Groin Node Metastases Following Surgery for Vulvar Cancer: A Systematic Review - Ferrari, Federico; Ismail, Lamiese; Sabbagh, Ahmad; Hardern, Kieran; Owens, Robert; Gozzini, Elisa; Soleymani Majd, Hooman (Oncology Reviews, 2024)
Background: Lymph node metastasis in vulvar cancer is a critical prognostic factor associated with higher recurrence and decreased survival. A survival benefit is reported with adjuvant radiotherapy but with potential significant morbidity. We aim to clarify whether there is high-quality evidence to support the use of adjuvant radiotherapy in this setting. Objectives: The aim of the study was to assess the effectiveness and safety of adjuvant radiotherapy to locoregional metastatic nodal areas. Search Methods: We conducted a comprehensive and systematic literature search of MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Google Scholar, ClinicalTrials.gov, and the National Cancer Institute. We considered only randomized controlled trials (RCTs). Main Results: We identified 1,760 records and finally retrieved only one eligible RCT (114 participants with positive inguinofemoral lymph nodes). All women had undergone radical vulvectomy and bilateral inguinal lymphadenectomy and had been randomized to adjuvant radiotherapy or to intraoperative ipsilateral pelvic lymphadenectomy without adjuvant radiotherapy. At 6 years, the overall survival (OS) was 51% versus 41% in favor of radiotherapy (HR 0.61; 95% CI 0.30–1.3) without significance and with very low certainty of evidence. At 6 year, the cumulative incidence of cancer-related deaths was 29% versus 51% in favor of adjuvant radiotherapy (HR 0.49; 95% CI 0.28–0.87). Recurrence-free survival at 6 years was 59% after adjuvant radiotherapy versus 48% after pelvic lymphadenectomy (HR 0.39; 95% CI 0.17–0.88). Three (5.3%) versus 13 (24.1%) groin recurrences were noted, respectively, in the adjuvant radiotherapy and pelvic lymphadenectomy groups. There was no significant difference in acute toxicities for pelvic lymphadenectomy compared to radiotherapy. In women with positive pelvic lymph nodes (20%), the OS at 6 year was 36% compared with 13% in favor of adjuvant radiotherapy. Late cutaneous toxicity rate appeared to be greater after radiotherapy (19% vs. 15%) but with less chronic lymphedema (16% vs. 22%). Conclusion: There is only very low-quality evidence on administering adjuvant radiotherapy for inguinal lymph node metastases. Although the identified study was a multicenter RCT, there was a reasonable imprecision and inconsistency because of small study numbers, wide confidence intervals in the data, and early trial closure, resulting in downgrading of the evidence.